An Analysis of Pick-up Lines in Social Media: A Semantic Study: (Analisis Kata Pikat dalam Media Sosial: Satu kajian Semantik) (Jurnal Bahasa, 2021)
This research is a semantics study of pick-up lines, using the theoretical approach of Mansoer Pateda (2001). This theory identifies of four aspects of meaning, that is, sense, feeling, tone and intention. New terms have emerged as 'pick-up lines' in social media, in line with modernization of the language. Pick-up lines are a strategy used by men to communicate with women whom they are attracted to with the intention of getting acquainted or beginning a relationship. Past research has mostly been carried out in Western countries, and there has not been any documented research conducted in Brunei thus far. Apart from this, there is also some confusion between pick-up lines and regular statements. To determine the aspect of meaning (Pateda, 2001), this study examines the characteristics found in several pick-up lines specifically made by Bruneians, selected by the researcher from two social media applications, Instagram and YouTube. The issue that arose is the extent to which the theoretical approach of Pateda (2001) suffices, that is, whether the four aspects of meaning can be seen in these pick-up lines. The characteristics of these pick-up lines is also studied. The findings of the study show all four aspects of meaning are present, based on the characteristics determined for each pick-up line, and at the same time, they play a clear role in understanding the meaning of the pick-up line intended by the speaker.Keywords: Pick-up lines, semantics, characteristics, aspects of meaning, social media